Managing hyponatraemia secondary to primary polydipsia: beware too rapid correction of hyponatraemia. Issue 8 (August 2017) - Boehm, Emma; Kumar, Shanal; Nankervis, Alison; Colman, Peter
Abstract: We describe three cases of severe hyponatraemia in the setting of primary polydipsia that were managed in our centre in 2016. Despite receiving different solute loads, large volume diuresis and rapid correction of serum sodium occurred in all cases. Given the potentially catastrophic consequence of osmotic demyelination, we highlight the judicious use of desmopressin and hypotonic fluid infusion to mitigate sodium overcorrection in this setting.